Emily Dickinson traduzida por José Lira e Augusto de Campos - Gama, Benedita Teixeira (2021)
This paper proposes a comparative study of the translations of four poems by the poet Emily Dickinson (1830-1886), performed in common by the writers/translators Augusto de Campos and José Lira. These poems are part of the books O Anticrítico (CAMPOS, 1986), Emily Dickinson: não sou ninguém (2008, 2015), in its two editions, Alguns poemas (2006) and A branca voz da solidão (2011). The first chapter discusses the conception of poetic translation that guides the work of both poet-translators, highlighting certain elements of the trajectory of the concrete poetry movement in Brazil, initiated by the Campos brothers and Décio Pignatari (CAMPOS, 1981, 2015), as well as the three main modalities of poetry postulated by Ezra Pound (1976). In the second part, we present the proposed translations into Portuguese of the poems “Sunset that screens, reveals”, “Oh honey of an hour”, “If recollecting were forgetting” and “For each ecstatic instant”, by Emily Dickinson, considering the translation solutions/choices assumed by these translation projects, as well as how they present themselves when confronted with the poetics of the author. As for the theoretical and methodological approach, we sought support for this comparative study in the propositions of Paulo Henriques Britto (2002, 2017) about poetic translations that find support in the correspondences and analogies between original and translation. Finally, both the translation projects and the profile of Emily Dickinson conveyed by the two Brazilian translators and poets are analyzed.